2018
DOI: 10.3390/nu10020209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Acute Exercise Bout on Serum Hepcidin Levels

Abstract: Iron deficiency is a frequent and multifactorial disorder in the career of athletes, particularly in females. Exercise-induced disturbances in iron homeostasis produce deleterious effects on performance and adaptation to training; thus, the identification of strategies that restore or maintain iron homeostasis in athletes is required. Hepcidin is a liver-derived hormone that degrades the ferroportin transport channel, thus reducing the ability of macrophages to recycle damaged iron, and decreasing iron availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
46
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 134 publications
(383 reference statements)
10
46
0
2
Order By: Relevance
“…Generally, physical exercises induce an increase in serum hepcidin concentrations during the early recovery phase [17]. In our study, the post-exercise hepcidin results (post) are consistent with earlier studies reporting significant changes in marathon runners [47].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Generally, physical exercises induce an increase in serum hepcidin concentrations during the early recovery phase [17]. In our study, the post-exercise hepcidin results (post) are consistent with earlier studies reporting significant changes in marathon runners [47].…”
Section: Discussionsupporting
confidence: 92%
“…During and after a 100 km run the regulation of hepcidin and iron metabolism can be controlled with two opposite metabolic pathways: first, the occurrence of inflammation and an increased IL-6 serum concentration which can induce hepcidin synthesis; and second, elevated erythropoiesis activity, which can suppress the elevation of this hormone in serum [15,16]. Thus, although IL-6 is an undoubted co-operator to the post-exercise hepcidin response, it seems that there are additional factors that cooperate during prolonged exercise to achieve the adequate level of this hormone [17].…”
Section: Introductionmentioning
confidence: 99%
“…Regular physical exercise is associated with numerous health benefits including a lower risk of all-cause mortality [37,38], nevertheless, strenuous exercise specially in amateur athletes, promotes the generation of oxidative stress and a pro-inflammatory state, which are one of the main reasons for the muscular aggression observed in high intensity exercise, together with other physiological alterations such as sports anemia [12], characterized by hematological changes including decrease in RBC, hemoglobin, and hematocrit [12,13,15]. These changes reduce oxygen supply and energy production which could regulate the aerobic performance capacity [17], which could lead to a reduction in the physical performance, incorrect adaptation to training protocols, and other possible physiological alterations [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, attention to hepcidin (an iron regulating hormone) has been growing as a key factor contributing to iron deficiency in endurance athletes (Badenhorst et al., 2016; Peeling et al., 2017). Sufficient evidence has revealed that various types of exercise increase the serum hepcidin level during the postexercise period (Badenhorst et al., 2015a; Domínguez et al., 2018; Goto, Kasai, Kojima, & Ishibashi, 2018; Goto, Sumi, Kojima, & Ishibashi, 2017; Peeling et al., 2017). Moreover, the increase in postexercise hepcidin level has been attributed to exercise‐induced increases in interleukin (IL)‐6 in iron sufficient individuals (Badenhorst et al., 2015a, 2015b; Peeling, 2010).…”
Section: Introductionmentioning
confidence: 99%